Contribution of Nilaparvata lugens Nicotinic Acetylcholine Receptor Subunits Toward Triflumezopyrim and Neonicotinoid Susceptibility. - Zhang, Y.C.; Zhuang, Z.X.; Zhang, F.; Song, X.Y.; Ye, W.N.; Wu, S.F.; Bass, C.; O'Reilly, A.O.; Gao, C. (Environmental Science and Technology, 2025)
Nicotinic acetylcholine receptors (nAChRs) are the molecular targets of some important insecticides including triflumezopyrim and neonicotinoids. However, our understanding of insect nAChR pharmacology and the specific nAChR subunits targeted by these insecticides remains limited. Here, we cloned 11 nAChR subunit genes, comprising Nl?1 to Nl?8, Nl?10, Nl?1 and Nl?3, from Nilaparvata lugens, a highly damaging insect pest of rice crops worldwide. Analysis of the expression of these genes in different tissues of N. lugens by qPCR analysis identified the brain as the primary site of expression. Knock down of the expression of Nl?1, Nl?2, Nl?8 and Nl?1 using RNAi reduced N. lugens sensitivity to triflumezopyrim, suggesting these genes encode potential target subunits for triflumezopyrim. Knock out of Nl?2 and Nl?8 nAChR subunits by CRISPR/Cas9 genome editing showed that their deletion significantly reduced the toxicity of triflumezopyrim toward N. lugens. Furthermore, the deletion of Nl?2 also increased N. lugens resistance to imidacloprid and dinotefuran. However, numerous attempts revealed that the Nl?1 knockout was nonviable. In vitro expression of receptors composed of Drosophila homologous subunits showed that this all-insect nAChR was inhibited by nanomolar concentrations of triflumezopyrim. The present findings identify specific nAChR subunits that are important both as targets for monitoring resistance-associated mutations and as subjects for molecular studies aimed at developing novel insecticides targeting these essential ion channels.